Clinically relevant variants identified in thoracic aortic aneurysm patients by research exome sequencing. Issue 5 (7th February 2016) - Schubert, Jeffrey A.; Landis, Benjamin J.; Shikany, Amy R.; Hinton, Robert B.; Ware, Stephanie M.
Abstract : Thoracic aortic aneurysm (TAA) is a genetically heterogeneous disease involving subclinical and progressive dilation of the thoracic aorta, which can lead to life‐threatening complications such as dissection or rupture. Genetic testing is important for risk stratification and identification of at risk family members, and clinically available genetic testing panels have been expanding rapidly. However, when past testing results are normal, there is little evidence to guide decision‐making about the indications and timing to pursue additional clinical genetic testing. Results from research based genetic testing can help inform this process. Here we present 10 TAA patients who have a family history of disease and who enrolled in research‐based exome testing. Nine of these ten patients had previous clinical genetic testing that did not identify the cause of disease. We sought to determine the number of rare variants in 23 known TAA associated genes identified by research‐based exome testing. In total, we found 10 rare variants in six patients. Likely pathogenic variants included a TGFB2 variant in one patient and a SMAD3 variant in another. These variants have been reported previously in individuals with similar phenotypes. Variants of uncertain significance of particular interest included novel variants in MYLK and MFAP5, which were identified in a third patient. In total, clinically reportable rare variants were found in 6/10 (60%) patients, with at least 2/10 (20%) patients having likely pathogenic variants identified. These data indicate that consideration of re‐testing is important in TAA patients with previous negative or inconclusive results. © 2016 Wiley Periodicals, Inc.